2022
DOI: 10.1182/blood.2021014956
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide promotes the development of TP53-mutated therapy-related myeloid neoplasms

Abstract: There is a growing body of evidence that therapy-related myeloid neoplasms (t-MNs) with driver gene mutations arise in the background of clonal hematopoiesis (CH) under the positive selective pressure of chemo- and radiation therapies (CRT). Uncovering the exposure relationships that provide selective advantage to specific CH mutations is critical to understanding the pathogenesis and etiololgy of t-MNs. In a systematic analysis of 416 patients with t-MN and detailed prior exposure history, we found that TP53 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 42 publications
3
61
0
Order By: Relevance
“…We first analyzed genome-wide allelic imbalances to include arm-level alterations detected by CBA. In agreement with prior studies [ 22 , 23 ], 365 (76%) had at least one chromosomal aberration including CK ( n = 190, 39.3%), MK ( n = 183, 37.90%), deletion 7q or monosomy 7 ( n = 148, 30.6%), deletion 5q or monosomy 5 ( n = 108, 22.4%), and deletion 17p across TP53 locus (referred to as 17p loss hereafter, n = 58, 12%) ( Figure S1A ) . We next analyzed the somatic mutation landscape of TP53 mut in t-MN.…”
Section: Resultssupporting
confidence: 93%
“…We first analyzed genome-wide allelic imbalances to include arm-level alterations detected by CBA. In agreement with prior studies [ 22 , 23 ], 365 (76%) had at least one chromosomal aberration including CK ( n = 190, 39.3%), MK ( n = 183, 37.90%), deletion 7q or monosomy 7 ( n = 148, 30.6%), deletion 5q or monosomy 5 ( n = 108, 22.4%), and deletion 17p across TP53 locus (referred to as 17p loss hereafter, n = 58, 12%) ( Figure S1A ) . We next analyzed the somatic mutation landscape of TP53 mut in t-MN.…”
Section: Resultssupporting
confidence: 93%
“…In multiple myeloma patients, there is contradictory data with respect to the Impact of CH on OS, with one study reporting an adverse impact, 26 while another reporting no impact 27 ; findings possibly altered by lenalidomide maintenance therapy, with lenalidomide being clearly associated with second primary malignancies. More recently however, a study has reported expansion of TP53 mutant hematopoietic stem cell clones after exposure to lenalidomide due to selective CK1 α (casein kinase) degradation and consequent p53‐mediated apoptosis of TP53 wild‐type cells 29 . Whether the increased occurrence of therapy‐related myeloid neoplasms (tMNs) in patients treated cytotoxic chemotherapy is secondary to expansion of pre‐existing CH clones or chemotherapy‐induced genotoxic stress is a matter of debate, but there is accumulating evidence to support the former hypothesis.…”
Section: Ch and Hematologic Malignanciesmentioning
confidence: 99%
“…The presence of CH can inform future therapeutic strategies for these patients; in particular, they should be factored in assessing risk versus benefit prior to adjuvant chemotherapy or radiation, and choice of future therapies in the event of progression. Screening prior to autologous hematopoietic stem cell transplant/CAR‐T: As noted above, presence of CH at the time of auto transplantation for lymphoma and myeloma predicts worse overall and progression‐free survival 24,26 . Screening prior to transplant can also inform future therapy options for patients such as those with multiple myeloma where lenalidomide (but not pomalidomide) has been shown to promote expansion of TP53 mutant hematopoietic stem cell clones 29 . Therefore, we recommend research‐based screening for CH in patients prior to autologous hematopoietic stem cell transplantation, especially in individuals >50 years of age, and in those patients with prior exposures to chemotherapy and/or radiation.…”
Section: Testing Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, lenalidomide degrades casein kinase 1 alpha (CK1α, encoded by CSNK1A1 gene) more efficiently than thalidomide and pomalidomide in myeloid neoplasms, thus providing a therapeutic window for lenalidomide in del (5q) MDS, where CSNK1A1 haploinsufficiency due to genetic deletion sensitizes tumor cells to lenalidomide ( 80 , 186 , 187 ). A recent study showed that treatment with lenalidomide but not pomalidomide leads to expansion of pre-leukemic Trp53 -mutant hematopoietic stem and progenitor cells (HSPCs) due to selective degradation of Ck1α, which offers a potential alternative strategy to mitigate the risk of therapy-related myeloid neoplasms (t-MNs) development ( 171 ). Accordingly, the efficacy and toxicity profiles of each IMiD and the precise use of these agents need to be thoroughly investigated.…”
Section: Development Of Imidsmentioning
confidence: 99%